2016
DOI: 10.1159/000447367
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Respiratory Diseases and Dietary Patterns Derived by Factor Analysis and Reduced Rank Regression

Abstract: Background/Aims: The study aims to identify children's dietary patterns and explore the relationship between dietary patterns and respiratory diseases. Methods: Subjects were 2,397 fourth graders in 14 Taiwanese communities who participated in the Taiwan Children Health Study. This study is based on an evaluation of dietary patterns, performed from April until June 2011. Information pertaining to respiratory disease was obtained by The International Study of Asthma and Allergies in Childhood questionnaire, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…They also had a higher consumption of sugar and carbonated beverages [37]. Lin et al (2016) used a factor analysis approach to show that children eating a "healthy" diet had lower rates of wheezing, allergic rhinitis, and bronchitis when compared to those on a high protein, high fat "Western" diet; however, this association was no longer significant after adjustment for confounders [38]. Lee et al used reduced rank regression methodology to identify a dietary pattern characterized by high consumption of fast foods, high-fat snacks, candy and cookies, and low consumption of fruit, vegetables and rice that was associated with increased risk of current and severe asthma [9].…”
Section: Discussionmentioning
confidence: 99%
“…They also had a higher consumption of sugar and carbonated beverages [37]. Lin et al (2016) used a factor analysis approach to show that children eating a "healthy" diet had lower rates of wheezing, allergic rhinitis, and bronchitis when compared to those on a high protein, high fat "Western" diet; however, this association was no longer significant after adjustment for confounders [38]. Lee et al used reduced rank regression methodology to identify a dietary pattern characterized by high consumption of fast foods, high-fat snacks, candy and cookies, and low consumption of fruit, vegetables and rice that was associated with increased risk of current and severe asthma [9].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with other study with factor analysis or principal component analysis, two dietary patterns were extracted by using factor analysis in cross-sectional study in Taiwan school-age children21. Both patterns were observed to be associated with and increased risk of allergic rhinitis, However, this study21 had some conflicts itself from the information presented: high-protein, high-fat, and western diet pattern was associated with increased risk of allergic rhinitis when score as the continuous variables but not when as categorical variables; the health pattern was seemed to be associated with an increased risk of rhinitis when pattern score takes as both continuous and categorical variables whereas the author did not provide any reason.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary pattern which represents a whole profile of a diet might be more useful to study the association between diet and health outcome, because dietary pattern can in some degree reflect the interactions among different foods or different nutrients1314. Current study found that both indexed-based patterns, such as the Mediterranean diet pattern15161718, and patterns defined by using posterior approaches19202122 might have impacts on asthma and other allergic sensitization. However, studies on the association between Mediterranean diet and rhinitis in school-aged children did not obtain conclusive results: for example, in adherence to a Mediterranean dietary pattern was inversely associated with rhinitis and other atopic disease in Mexican children15 and Greece children23, whereas such association was not observed in Turkey children2425.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…High fat diet is not only associated with type 2 diabetes (T2DM), hypertension and other metabolic diseases, but is also studied to be correlating significantly with asthma and other respiratory diseases. Based on the previous studies, the incidence of asthma and asthmatic diseases in children with high-fat diet is significantly higher than children without high-fat diet [1,2] however, the pathogenicity underpinning high-fat diet with asthma is still in the mystery. Asthma is a chronic airway inflammatory disease, which often occurs with airway remodeling [3,4].…”
Section: Introductionmentioning
confidence: 99%